INFLUENCE EFFECTIVENESS ONLINE LEARNING AGAINST INDEPENDENCE STUDY MEDIATED MOTIVATION INTRINSIC IN PARTICIPANTS EDUCATE CLASS XI IPS SMA NEGERI 2 BABELAN - Sellyana (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The purpose of this study is to find out the influence of online learning effectiveness on independent learning mediated by intrinsic motivation for XI IPS students at SMA Negeri 2 Babelan . Quantitative statistical approach with a correlational approach were employed in this research. The population of this study consists of 180 students from class XI IPS SMA Negeri 2 Babelan . With a 5% error rate, the research sample was determined to be 124 students using the Isaac and Michael table formula. A survey method in the form of a research questionnaire utilizing Google Form was used to collect primary data. Data was analyzed using IBM SPSS Statistics Version 26 and the path analysis approach. The findings revealed online learning effectiveness (X) had no significant effect on intrinsic motivation (M), intrinsic motivation (M) had a significant effect on learning independence (Y), and online learning effectiveness (X) had a significant effect on independent learning (Y). Other research shows that intrinsic motivation (M) is unable to mediate the influence of online learning effectiveness (X) on independent learning (Y).